Hemodynamic instability during anesthesia in an adolescent with Loeys‐Dietz syndrome: a case report. Issue 12 (9th September 2014) - Bunting, Alexandra C.; Bould, M. Dylan; Polaner, David
Summary We present a case of a 12‐year‐old male with Loeys‐Dietz syndrome (LDS), a rare life‐threatening genetic disorder. Multiple manifestations of LDS were present, including easy bruising, aortic root dilatation, multiple areas of vessel tortuosity, and joint laxity. The patient's medications included a beta‐blocker and an angiotensin II receptor antagonist for prophylaxis against further aortic root dilatation due to his LDS. He experienced intraoperative hemodynamic instability and became pulseless during an orthopedic procedure, which had to be abandoned. Anesthesia was reattempted 2 days after cessation of the patient's antihypertensive medications and was successful with only minor postoperative hypertension.